The Effect Of Moringa Leaves And Banana (Morina) Cookies On Blood Pressure In Hypertensive Patients - Laily Fitri Handayani; Suhaema Suhaema; Retno Wayuningsih; Ni Ketut Sri Sulendri (Poltekkes Kemenkes Mataram, 2024)
Background: Hypertension is a disease that often does not cause symptoms until the sufferer's condition worsens. This disease has become one of the main causes of death globally. Various methods continue to be sought to manage blood pressure. Apart from appropriate medication, it is also recommended to adopt a healthy lifestyle by choosing nutritious foods as recommended in the Dietary Approach to Stop Hypertension.Objective: Evaluating the effect of Morina cookies on the blood pressure of individuals with hypertension.Research Methods: This research uses the Randomized Controlled Trial method with a Pretest-Posttest design including a control group. The number of subjects was calculated using the Lemeshow formula, resulting in 28 subjects.Research Result: In subjects aged 45-80 years, with 82% being female, both systolic and diastolic blood pressure decreased after the intervention (p<0.05).Conclusion: There was a significant reduction in systolic and diastolic blood pressure after administering Morina cookies for 7 days in hypertensive patients.